Parents' Experience and Satisfaction in Neonatal Intensive Care Units in Ethiopia: A Multicenter Cross-Sectional Study Using an Adapted Version of EMPATHIC-N - Gulo, Berhanu; Miglierina, Laura; Tognon, Francesca; Panunzi, Silvia; Tsegaye, Ademe; Asnake, Tina; Manenti, Fabio; Dall'Oglio, Immacolata (Frontiers in Pediatrics, 2021)
Background: In neonatal intensive care units (NICU) setting, parents’ experience and satisfaction permit to evaluate clinical practice and improve the care of infants and parents. Little is known about this topic in low resource settings. The aim of this study was to explore parents’ experience and satisfaction with the care received in the NICUs across three different NICU levels in Ethiopia, using a translated, culturally adapted and validated local language version of EMpowerment of PArents in THe Intensive Care-Neonatology (EMPHATIC-N) questionnaire. Methods: This was a cross-sectional multicenter study. The participants were the parents of infants discharged from one of the NICUs located in three different hospitals. The two local language versions of Empathic-N with 38 items were developed, adapted and validated. Differences between the NICU levels were investigated in the five questionnaire domains. In addition, four general questions about overall experience and satisfaction were also formulated. Qualitative data were collected using four open-ended questions. Results: Almost all the parents answered to the questionnaire (93.9%, n=386). Questionnaire items on satisfaction on average scored more than four. The highest mean scores were obtained for Parental participation (median: 5.17; iqr: 4.67-5.62), while they were lower for Organization/Hospital environment (median: 4.67; iqr:4.33-5.17). Different levels of parent satisfaction were observed across the three NICU levels showing a statistically higher satisfaction in level II NICU compared to the other levels. Level of education, place of residence and length of stay were associated with parental satisfaction and experience. Conclusion: This study validated two Ethiopian versions of the EMPATHIC-N questionnaire to assess parents’ experience and satisfaction during their child’s stay in the NICU. The differences found across the three levels of NICU suggest the need to further investigate the determinants of satisfaction.